2018
DOI: 10.11646/zootaxa.4403.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and morphological resolution of the Helobdella stagnalis species-complex (Annelida: Clitellata: Hirudinea)

Abstract: The glossiphoniid freshwater leech, Helobdella stagnalis, was described by Linnaeus 1758 based on common European specimens. The presence of a brown, chitinous scute on the dorsal-anterior surface, as observed on leeches elsewhere in the world, has generally led to the classification of all scute-bearing members of the genus as H. stagnalis. Here we describe the morphology and behavior of the type species from Europe, and analyze H. stagnalis-like specimens collected worldwide. We present evidence for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Although we cannot exclude the possibility that these differences reflect culture conditions that were sub-optimal for H. octatestisaca , the average life-span of H. octatestisaca in this experiment (246 days) was not less than that of H. robusta under similar conditions (229 days), and several of the animals survived after laying their last clutch of embryos for periods of time that were much longer than the average inter-clutch interval. The difference in the degree of iteroparity between H. robusta and H. octatestisaca is also consistent with the fact that, within the genus Helobdella , molecular phylogenies place H. robusta and H. triserialis in one species complex, the "triserialis" series, and most of the scute-bearing species, including H. octatestisaca into a paraphyletic "stagnalis" series (Oceguera-Figueroa et al, 2010;Saglam et al 2018).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Although we cannot exclude the possibility that these differences reflect culture conditions that were sub-optimal for H. octatestisaca , the average life-span of H. octatestisaca in this experiment (246 days) was not less than that of H. robusta under similar conditions (229 days), and several of the animals survived after laying their last clutch of embryos for periods of time that were much longer than the average inter-clutch interval. The difference in the degree of iteroparity between H. robusta and H. octatestisaca is also consistent with the fact that, within the genus Helobdella , molecular phylogenies place H. robusta and H. triserialis in one species complex, the "triserialis" series, and most of the scute-bearing species, including H. octatestisaca into a paraphyletic "stagnalis" series (Oceguera-Figueroa et al, 2010;Saglam et al 2018).…”
Section: Resultssupporting
confidence: 79%
“…OTU3, collected from the same location as OTU2, is a H. stagnalis -like species , as defined by the presence of a nuchal scute on the dorsal surface at the boundary between the rostral and midbody segments. Molecular phylogenies have revealed that the morphologically defined H. stagnalis is in fact a complex of species (Beresic-Perrins 2017;Oceguera-Figueroa et al 2010;Saglam et al, 2018); CO1 sequencing indicates that the species used here is H. octatestisaca (Hoc; Lai et al 2014). For molecular identification, the cytochrome oxidase 1 (CO1) sequences for the species used here are available as GenBank accession numbers: Hau, MH729328; Hro, MH729330; Hoc, MH729329).…”
Section: Animalsmentioning
confidence: 92%
See 1 more Smart Citation
“…The Helobdella Blanchard, 1896 taxonomic status has changed since the morphological species descriptions by Klemm (1985) and Sawyer (1986), and with the advent of molecular phylogenetic studies (Siddall et al, 2005;Bely & Weisblat, 2006;Moser et al, 2011Moser et al, , 2013Kutschera et al, 2013). More recent efforts demonstrated even larger changes, with Beresic-Perrins et al (2017) studying a unique site and adjacent drainages in the Colorado River Basin, and Saglam et al (2018) describing the anatomy of 5 new species. Recently, Iwama et al (2019) described the Sweden neo-type specimen of H. stagnalis and noted 6 new genetic forms over a large geographical range.…”
Section: Comparison Of Helobdella Stagnalis and H Californicamentioning
confidence: 99%
“…With the recent surge of works, we resurrected the drawings made at that time and compared them to the findings of Salas-Montiel et al 2014, Beresic-Perrins et al (2017), and Saglam et al (2018), noticing the Utah and Nevada anatomical features were unlike any in these illustrations. This paper first describes in more detail our reference species H. californica.…”
Section: Comparison Of Helobdella Stagnalis and H Californicamentioning
confidence: 99%